Application Of Ziwbbm In Government Agency - Ika Prasetya Triwahyudi B.; Pompong B. Setiadi; Sri Rahayu (International Publisher, 2022)
The challenges of globalization today have implications for changes in various organizational life arrangements. Development of Integrity Zones in realizing organizations that have a great commitment to providing services to the community, especially government agencies is very necessary, the application of ZIWBBM to government agencies. Quantitative research method, this type of research is associative with a total population of 74 employees in one of the government agencies, the sampling technique uses total sampling, with primary data sources with questionnaires. The analysis technique used was multiple linear regression with t test and F test. The results showed that the partial and simultaneous application of ZIWBBM had a significant positive effect on employee performance, this was evidenced by a significance value < 0.005. It is hoped that the results of research at this government agency can be used as an evaluation and pay attention to the application of ZIWBBM in order to improve service performance.